2016
DOI: 10.1097/mpg.0000000000001154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin E With Therapeutic Iron Supplementation on Iron Repletion and Gut Microbiome in US Iron Deficient Infants and Toddlers

Abstract: Background Iron therapy induces inflammation which could decrease iron absorption. Increased exposure of iron in the gut could also alter microbiome file. Providing antioxidants such as vitamin E with iron therapy has been associated with reduced oxidative potential. Objective Test the efficacy of adding vitamin E to therapeutic iron therapy on iron repletion, inflammation markers and gut microbiome in iron deficient infants and toddlers. Design This was a randomized, double-blind, control trial in which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 43 publications
1
36
0
2
Order By: Relevance
“…The four predominant phyla observed in this study were comparable to previous studies conducted by our group [ 9 , 29 ] and others [ 30 ]. However, we found a higher abundance of Proteobacteria at 38% compared with other studies [ 11 , 30 ] that reported typical abundances less than 10%.…”
Section: Discussionsupporting
confidence: 92%
“…The four predominant phyla observed in this study were comparable to previous studies conducted by our group [ 9 , 29 ] and others [ 30 ]. However, we found a higher abundance of Proteobacteria at 38% compared with other studies [ 11 , 30 ] that reported typical abundances less than 10%.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the MNP composition in Kenya contained additional micronutrients that favored beneficial gut flora. In a recent trial in US children aged 9–24 mo who were receiving therapeutic iron supplementation for iron deficiency, the addition of vitamin E to the iron supplement beneficially affected the gut microbiome, including a decrease in the relative abundance of Bacteroides and an increase in the beneficial butyrate producers Lachnospiraceae and Roseburia (31). These findings suggest that the addition of antioxidants, prebiotics, or probiotics to MNPs may overcome the proinflammatory changes in the intestine and microbiota that have been shown with iron supplementation (3234).…”
Section: Discussionmentioning
confidence: 99%
“…Given that bacteria can secrete small molecules known as siderophores that can solubilize iron for host cells (Deriu et al 2013), the opportunity is present for resident bacteria to modulate host immune responses at the mucosal interface. Iron has also been shown to modulate butyrate-producing bacteria (Tang et al 2016), as well as pathogenic Proteobacteria (Kamada et al 2013). Whether iron deficiency has a direct effect on early microbiota colonization and inflammation is a hypothesis worthy of further study.…”
Section: The Importance Of Proteobacteria To Immune Education In Earlmentioning
confidence: 99%